The Methylene Alkoxy Carbamate Self‐Immolative Unit: Utilization for the Targeted Delivery of Alcohol‐Containing Payloads with Antibody–Drug Conjugates. (20th May 2016) - Kolakowski, Robert V.; Haelsig, Karl T.; Emmerton, Kim K.; Leiske, Chris I.; Miyamoto, Jamie B.; Cochran, Julia H.; Lyon, Robert P.; Senter, Peter D.; Jeffrey, Scott C.
Abstract: A strategy for the conjugation of alcohol‐containing payloads to antibodies has been developed and involves the methylene alkoxy carbamate (MAC) self‐immolative unit. A series of MAC β‐glucuronide model constructs were prepared to evaluate stability and enzymatic release, and the results demonstrated high stability at physiological pH in a substitution‐dependent manner. All the MAC model compounds efficiently released alcohol drug surrogates under the action of β‐glucuronidase. To assess the MAC technology for ADCs, the potent microtubule‐disrupting agent auristatin E (AE) was incorporated through the norephedrine alcohol. Conjugation of the MAC β‐glucuronide AE drug linker to the anti‐CD30 antibody cAC10, and an IgG control antibody, gave potent and immunologically specific activities in vitro and in vivo. These studies validate the MAC self‐immolative unit for alcohol‐containing payloads within ADCs, a class that has not been widely exploited.